FREQUENCY OF SPORT ACTIVITY PARTICIPATION OF SLOVENES - Maja Pori; Boris Sila (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2010)
The objective of the study was to investigate the frequency of participation in sport activity of Slovenes. The sample consisted of 1286 persons, 54% were women and 46% were men. To obtain the necessary data a questionnaire method was used. We focused on two groups of questions. The first group reffered to participation in sport activity in general (frequency of any sport activity) and the second group reffered to participation in a particular sport. The results show that 33% of Slovenes were regularly active, 31% occasionally active and 36% non-active. They were the most active in the following sport activities: walking, swimming, cycling, alpine skiing and mountaineering.